2020
DOI: 10.3390/biom10081114
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Hotspot Residues Involved in Allosteric Signal Transmission in Pro-Apoptotic Peptide—Mcl1 Complexes

Abstract: Mcl1 is a primary member of the Bcl–2 family—anti–apoptotic proteins (AAP)—that is overexpressed in several cancer pathologies. The apoptotic regulation is mediated through the binding of pro-apoptotic peptides (PAPs) (e.g., Bak and Bid) at the canonical hydrophobic binding groove (CBG) of Mcl1. Although all PAPs form amphipathic α-helices, their amino acid sequences vary to different degree. This sequence variation exhibits a central role in the binding partner selectivity towards different AAPs. Thus, constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Previous studies that aimed to understand the Mcl-1−peptide interactions or to develop selective small molecule inhibitors focused on hot spot residues. 62,63 However, many studies have shown that in addition to the interaction of the hydrophobic face of the proapoptotic BH3 amphipathic helix with the exposed hydrophobic patch of anti-apoptotic Bcl-2 protein, hydrophilic interactions between specific residues play a major role in giving specificity to the pro-apoptotic Bcl-2 proteins. 33,64,65 Techniques such as FACS and deep sequencing were used to obtain high-throughput data on protein−peptide binding.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that aimed to understand the Mcl-1−peptide interactions or to develop selective small molecule inhibitors focused on hot spot residues. 62,63 However, many studies have shown that in addition to the interaction of the hydrophobic face of the proapoptotic BH3 amphipathic helix with the exposed hydrophobic patch of anti-apoptotic Bcl-2 protein, hydrophilic interactions between specific residues play a major role in giving specificity to the pro-apoptotic Bcl-2 proteins. 33,64,65 Techniques such as FACS and deep sequencing were used to obtain high-throughput data on protein−peptide binding.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Anti-apoptotic Bcl-2 proteins have been the targets of cancer therapy for many years, and efforts to develop efficient inhibitors have resulted in many promising compounds. ,, One of the strategies is to use the BH3 peptides of pro-apoptotic Bcl-2 proteins to antagonize the anti-apoptotic Bcl-2 members, and thus, the cellular death pathway can be activated in cancer cells. ,, Although several pro-apoptotic BH3 peptides have affinity for anti-apoptotic proteins at the nanomolar level, the BH3 peptide inhibitors have cross reactivity with many anti-apoptotic Bcl-2 partners. , Efforts to synthesize BH3-mimetic peptides that have stable helical structure and enhanced affinity for specific anti-apoptotic Bcl-2 proteins have yielded mixed results. ,, These studies focused mainly on the hydrophobic face of the amphipathic BH3 helix. Previous studies that aimed to understand the Mcl-1–peptide interactions or to develop selective small molecule inhibitors focused on hot spot residues. , However, many studies have shown that in addition to the interaction of the hydrophobic face of the pro-apoptotic BH3 amphipathic helix with the exposed hydrophobic patch of anti-apoptotic Bcl-2 protein, hydrophilic interactions between specific residues play a major role in giving specificity to the pro-apoptotic Bcl-2 proteins. ,, Techniques such as FACS and deep sequencing were used to obtain high-throughput data on protein–peptide binding . As part of the strategy to use structure-based design, high-affinity peptide binders were designed on the basis of “recurring tertiary structural motifs” from known protein structures available in the PDB and this was applied to Bcl-X L , Mcl-1, and Bfl-1 proteins .…”
Section: Discussionmentioning
confidence: 99%
“…MMPBSA.py script from AmberTools is a fast method to compute binding free energy compared to other methods (Marimuthu et al, 2020), such as Replica-Exchange Free-Energy Perturbation (Fratev and Sirimulla, 2019) and umbrella sampling (Kumar et al, 1992). MMPBSA.py script was used to calculate binding free energy values between the spike protein and ACE2 for the representative structure and its mutated structures from alanine screening.…”
Section: Binding Free Energy Calculationmentioning
confidence: 99%